Civil society of Western Ukraine and Europe in the context of the Ukrainian Holodomor events of 1932-1933 - Богдан Левик (Cхід, 2023)
The article examines the Holodomor national tragedy of 1932-1933 in the context of the reaction to it by the population of neighboring Ukraine and more distant countries, as well as international organizations. It is emphasized that the Holodomor was a deliberate action of the communist authorities against the Ukrainian peasantry as a source of disobedience to the authorities and national resistance. It is shown that despite the efforts of the Bolshevik government to hide the glaring facts of the famine and the conformist support of the majority of foreign journalists accredited in the USSR, this information still received publicity in the world thanks to individual journalists of influential British newspapers and the work of foreign embassies and consulates in the USSR. It provoked a civil wave of help in various countries, but did not cause official condemnation of the Bolshevik policy by the member states of the League of Nations and the Catholic Church as an influential player in the international politics of the time. The role of public organizations and the Ukrainian Greek Catholic Church in the organization of assistance to illegal refugees from Ukraine and protest movements condemning the policy of the USSR towards Ukrainian peasants is considered. It was concluded that the first and subsequent recognitions of the Holodomor of 1932-1933 in Ukraine as genocide at the level of influential countries and international organizations, as well as the criminal proceedings carried out in Ukraine on the fact of committing the crime of genocide of 1932-1933 in Ukraine as a crime against humanity permit modern Ukrainians not only to consolidate the memory of the Holodomor as a significant historical narrative for the entire society, but also to re-understand this traumatic experience, renewing the nation and its values and outlook guidelines.